DIFFERENCES IN THE EFFECTIVENESS OF SELECTIVE ALPHA BLOCKER THERAPY COMBINED WITH 5-ALPHA REDUCTASE INHIBITOR ON IPSS VALUE OF BPH LUTS PATIENTS - Wahyudi, Septa Surya; Probosutiksna, Nuno Febrian; Suswati, Enny (Indonesian Urological Association, 2020)
Objective: The purpose of this study is to know the differences in effectiveness between SAB administration with combination 5-ARI administration assessed by IPSS evaluation in BPH LUTS patients. Material & Methods: This observational analytic with a cross-sectional design study had been done to 50 BPH LUTS patients that obtained at Paru Jember, Bina Sehat Jember, and Bhayangkara Bondowoso Hospital. These samples had got by simple random sampling method and include in inclusion with exclusion criteria freely. Results: This comparison study between the type of medical therapy administration and total IPSS decrease, IPSS-voiding decrease, IPSS-storage decrease, IPSS-QoL, and prostate volume give significancies as follows: p=0.002; p<0.001; p<0.001; p<0.05; p<0.001. Conclusion: There are significant differences between the type of medical therapy (SAB or 5-ARI combination) and total IPSS decrease, IPSS-voiding decrease, IPSS-storage decrease, IPSS-QoL, and prostate volume.